Tradicionais e novos atrativos nos balneários turísticos na Franças e no Nordeste do Brasil - Alexandre Queiroz Pereira; Bertrand Cozic; Eustogio Dantas (Confins)
Throughout the 20th century, tropical areas became increasingly more attractive, and today they represent places of international prominence for the practice of tourism and leisure activities. Therefore, aware of the coexistence of generations of seaside resorts, this article proposes to understand the role of nautical practices, marinas and golf courses in the formation or reinvention of tourist and seaside resorts in the northeastern region of Brazil. The results present the organization of the Fortaleza, Recife, Salvador. The development of secondary residences follows the same pattern, but we can see that the development of new activities such as nautical activities, with marinas, and golf courses are still practices that are few developed in the region and reserved to a restricted public of users. The analysis of two examples from France shows how these activities could become fundamental in the evolution of seaside resorts and the urban territories that host them.